Case Report: Rare primary bronchogenic acinic cell carcinoma in a pediatric patient - Sun, Yuxing; Zhou, Jun; Zhu, Jiaojiao; Li, Ming; Yang, Shiwu; Bin, Songtao; Tan, Li (Frontiers in Oncology, 2025)
Acinic cell carcinoma (AciCC) is an uncommon tumor of the salivary glands, with primary bronchogenic cases being particularly rare, especially in children. This report presents a case of a 3-year and 11-month-old boy who exhibited symptoms of cough and fever. Contrast-enhanced CT imaging revealed a solid mass in the right upper lung lobe accompanied by atelectasis, with poor bronchial visualization and no abnormal enhancement. Bronchoscopy identified a tumor obstructing the right upper lobe bronchial orifice. Surgical resection was performed, and histopathological analysis confirmed acinic cell carcinoma without lymph node involvement. The patient remained recurrence-free during an 18-month follow-up. Pediatric primary bronchial AciCC is exceptionally rare and typically manifests with non-specific symptoms. Radiological findings such as solid lung lesions or atelectasis may lead to misdiagnosis as pneumonia. However, complete surgical excision generally yields favorable outcomes.